Risk factors for recurrence after sublobar resection in patients with small (2 cm or less) non-small cell lung cancer presenting as a solid-predominant tumor on chest computed tomography - Moon, Youngkyu; Sung, Sook Whan; Moon, Seok Whan; Park, Jae Kil (Journal of Thoracic Disease, 2016)
Background: Sublobar resection is considered controversial for non-small cell lung cancer (NSCLC) presenting as a solid-predominant nodule. The aim of this study was to identify risk factors related to recurrence in small-sized NSCLC presenting as a solid-predominant nodule. Methods: We conducted a retrospective chart review of 118 patients who were treated for clinical N0 NSCLC sized ≤2 cm and who underwent sublobar resection with clear resection margins. We assigned them to two groups according to radiologic features: ground glass opacity (GGO)-predominant tumor and solid-predominant tumor. Clinicopathological characteristics and survival were analyzed in both groups. Risk factors for recurrence were analyzed in the solid-predominant tumor group. Results: Seventy-three patients had a GGO-predominant tumor, and 45 patients had a solid-predominant tumor. Five-year recurrence-free survival (RFS) in the solid-predominant tumor and GGO-predominant tumor groups was 64.9% and 95.5%, respectively. A multivariate analysis was performed to determine factors associated with recurrence after sublobar resection in the solid-predominant tumor group; it indicated that SUVmax [hazard ratio (HR) =1.482, 95% confidence interval (CI): 1.123–1.956, P=0.005] and histologic types other than adenocarcinoma (squamous cell carcinoma, HR =8.789, 95% CI: 1.572–49.134, P=0.013; other types, HR =53.569, 95% CI: 2.616–1096.849, P=0.010) were significant risk factors for recurrence. Conclusions: Risk factors in solid-predominant tumors sized ≤2 cm after sublobar resection are a high SUVmax and histologic types other than adenocarcinoma. Thus, lobectomy should be considered for solid-predominant NSCLC sized ≤2 cm with a high SUVmax or non-adenocarcinoma types.